The functional–formal impasse in (trust) property. Issue 3 (29th August 2017) - Wall, Jesse
Abstract: This paper identifies an impasse between two conceptions of 'property rights'. Formal conceptions explain 'property rights' in terms of an alienable right to exclude, that has moral significance in terms of individuals' preference satisfaction, and describe a trust beneficiary as having a right against the trustees' right. Functional conceptions explain a 'property right' in terms of the entitlements in a resource, which has moral significance in terms of a range of individual and social values, and describe a trust beneficiary as having a share in entitlements in the resource. This impasse has general implications for the normative analysis of property law and particular implications for the practical application of redistributive statutory provisions to discretionary trusts. The solution to this impasse lies in the abandoning the language of 'property' when we are concerned with the entitlements in a resource.